A STUDY OF REGISTERS USED DURING THE AUCTION OF DIE-CAST TOYS MALANG ON FACEBOOK - BRINDA, SONYA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Sociolinguistics, Register, Auction of Die-cast, Die-cast Toys Malang on Facebook.Humans live together as society and humans need language to comunicate with others. People create group of societies based on region, interest, social class, religion and many others. In specific group people create their own terms in theircommunity which is called register. In this study, the writer conducted a studyabout register used during the auction of die-cast toys Malang on facebook. Thereare two problems of the study, they are (1) What are the registers used by Die-castToys Malang when they do the auction on facebook?; (2) What are the contextualfactors influencing the registers used by the members of Die-cast Toys Malangwhen they do the auction on facebook?In this study, the writer used a qualitative approach. The data are utterances which contain registers. In collecting the data, the writer acted as a passive participant who only watched and captured the conversation during the auction, listed the register found during the observation, and did an interview. In the data analysis, the writer classified the register into a table to define the common sense and particular sense, the writer used the theory about contextual factors by Brown and Attardo (2009), checking the validity of the register found by asked to the admin of Die-cast Toys Malang community, and drawing conclusion.The writer found 21 registers used by the members of Die-cast Toys Malang Community on Facebook. There are 6 which have common sense, and 15 which have particular sense of registers. Then, some registers related to selling process, the condition from the package of Hot Wheels, and calling from the bidder who waits until the end of the auction.For further study in register, the writer suggests for the future researchers who want to conduct a study on register phenomena analyze it in other communities, such as photography community with the different analysis, such as critizing the utterances within Pragmatics field or analyzing under Second Language Acquisition dealing with grammatical error.